2010
DOI: 10.1016/j.vetpar.2009.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Limited genetic diversity among Sarcocystis neurona strains infecting southern sea otters precludes distinction between marine and terrestrial isolates

Abstract: Sarcocystis neurona is an apicomplexan parasite identified as a cause of fatal neurological disease in the threatened southern sea otter (Enhydra lutris nereis). In an effort to characterize virulent S. neurona strains circulating in the marine ecosystem, this study developed a range of markers relevant for molecular genotyping. Highly conserved sequences within the 18S ribosomal gene array, the plastid-encoded RNA polymerase (RPOb) and the cytochrome c oxidase subunit 1 mitochondrial gene (CO1) were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 42 publications
6
60
1
5
Order By: Relevance
“…Subsequent immunologic analysis of a collection of 14 S. neurona strains using antiserum against SnSAG1 demonstrated that this surface antigen is not expressed by multiple strains, and the lack of expression was shown to be due to the absence of the SnSAG1 gene (Howe et al, 2008). Those parasite strains that lack SnSAG1 were found to express one of two alternative major surface antigens that were call SnSAG5 and SnSAG6 (Crowdus et al, 2008; Wendte et al, 2010b). While it is conceivable that additional alternative major SnSAG paralogues exist, analysis of much more extensive collections of parasite strains suggest that SnSAG1, SnSAG5, or SnSAG6 will be predominant in the S. neurona strains circulating in nature (Rejmanek et al, 2010 , ; Wendte et al, 2010a).…”
Section: In Vitro Cultivation Cell and Molecular Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent immunologic analysis of a collection of 14 S. neurona strains using antiserum against SnSAG1 demonstrated that this surface antigen is not expressed by multiple strains, and the lack of expression was shown to be due to the absence of the SnSAG1 gene (Howe et al, 2008). Those parasite strains that lack SnSAG1 were found to express one of two alternative major surface antigens that were call SnSAG5 and SnSAG6 (Crowdus et al, 2008; Wendte et al, 2010b). While it is conceivable that additional alternative major SnSAG paralogues exist, analysis of much more extensive collections of parasite strains suggest that SnSAG1, SnSAG5, or SnSAG6 will be predominant in the S. neurona strains circulating in nature (Rejmanek et al, 2010 , ; Wendte et al, 2010a).…”
Section: In Vitro Cultivation Cell and Molecular Biologymentioning
confidence: 99%
“…In 2010, a panel of gene-specific molecular markers of varying phylogenetic resolution was developed to increase the discriminatory power of the molecular markers used for Sarcocystis population genetic analyses. This work established a comprehensive multi-locus sequence typing (MLST) approach capable of resolving strains at the genus, species and intra-species level (Wendte et al, 2010b; Rejmanek et al, 2010). The markers consisted of a plastid-encoded RNA polymerase b gene (RPOb) and a cytochrome c oxidase 1 (CO1) gene encoded within the apicoplast and mitochondrial organellar genomes respectively, both of which are maternally inherited and exist as useful markers to detect genetic exchange (or hybridization) between strains based on incongruity between nuclear and organellar genome phylogenies.…”
Section: In Vitro Cultivation Cell and Molecular Biologymentioning
confidence: 99%
“…The gene coding for caseinolytic protease (clpC) (a member of the chaperone family) is a conserved apicoplast gene that is widely applied in phylogenetic reconstructions of apicomplexan organisms (RATHORE et al, 2001;MARTINSEN et al, 2008;LAU et al, 2009). The plastid-encoded beta subunit of RNA polymerase (rpoB), which is responsible for processing polymerase activity, has also been used in phylogenetic reconstructions among organisms of the Sarcocystidae family (DUBEY et al, 2003a;WENDTE et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Entre a análise de amostras fecais, apenas uma amostra (5%) se mostrou positiva para ELLIS et al, 2000;GONDIM et al, 2004;DAHLGREN, 2011;) e outros grupos de protozoários, como organismos do gênero (TANHAUSER et al, 1999;REJMANECK et al, 2010;MILLER et al, 2010;WENDTE et al, 2010;WÜNSCHMANN et al, 2010).…”
Section: Discussionunclassified
“…Atualmente, a região ITS-1 vêm sendo muito utilizada para identificar e determinar prevalência de infecção em gambás por S. neurona (REJMANECK et al, 2009;REJMANECK et al, 2010), distinção entre S. neurona e S. falcatula, assim como entre outros coccídeos formadores de cisto tecidual e identificação de novos possíveis hospedeiros intermediários para S. neurona e S. falcatula MILLER et al, 2010;WENDTE et al, 2010;WÜNSCHMANN et al, 2010). O que demonstra a possibilidade de diferenciação das espécies em questão, porém devido à diversidade genética observada, muitos autores argumentam a necessidade do uso de marcadores complementares para esta finalidade.…”
Section: Região Espaçadora Transcrita Interna Do Rdna (Its-1)unclassified